2016
DOI: 10.1523/jneurosci.2673-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Accumbens nNOS Interneurons Regulate Cocaine Relapse

Abstract: Relapse to drug use can be initiated by drug-associated cues. The intensity of cue-induced relapse is correlated with the induction of transient synaptic potentiation (t-SP) at glutamatergic synapses on medium spiny neurons (MSNs) in the nucleus accumbens core (NAcore) and requires spillover of glutamate from prefrontal cortical afferents. We used a rodent self-administration/ reinstatement model of relapse to show that cue-induced t-SP and reinstated cocaine seeking result from glutamate spillover, initiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 69 publications
7
123
1
Order By: Relevance
“…Since mGluR5 has predominantly perisynaptic localization, the efficacy of mGluR5 antagonists to inhibit drug seeking is hypothesized to arise from preventing the actions of synaptic glutamate spillover produced during a drug seeking event, and at least for cocaine reinstatement there is a critical involvement of mGluR5 expressed on accumbens interneurons that selectively express neuronal nitric oxide synthase (nNOS) (Smith et al, 2017). …”
Section: Glutamate Spillover and Transient Synaptic Plasticity (T-mentioning
confidence: 99%
See 1 more Smart Citation
“…Since mGluR5 has predominantly perisynaptic localization, the efficacy of mGluR5 antagonists to inhibit drug seeking is hypothesized to arise from preventing the actions of synaptic glutamate spillover produced during a drug seeking event, and at least for cocaine reinstatement there is a critical involvement of mGluR5 expressed on accumbens interneurons that selectively express neuronal nitric oxide synthase (nNOS) (Smith et al, 2017). …”
Section: Glutamate Spillover and Transient Synaptic Plasticity (T-mentioning
confidence: 99%
“…Given the capacity of mGluR5 antagonists in the NAcore to prevent reinstated drug seeking (Olive, 2009) and the location of these receptors largely outside of the synaptic cleft (Mitrano and Smith, 2007), mGluR5 is a likely target of glutamate spillover. Recently it was shown that cue-induced cocaine seeking is critically dependent on mGluR5 located on a small population of NAc interneurons expressing nNOS, and that mGluR5 stimulation of nitric oxide production activates MMP-2,9 via nitrosylation (Smith et al, 2017). As described above, activated MMP-2,9 signals transient potentiation in NAcore MSNs.…”
Section: Glutamate Spillover and Transient Synaptic Plasticity (T-mentioning
confidence: 99%
“…After days to weeks of self-administration, the drug-seeking response is extinguished and subsequently reinstated by one of the stimuli known to cause relapse in humans, such as stress, contextual and/or discrete drug-associated cues, or the drug itself (for review, see Epstein et al 2006). Synaptic release of glutamate in the nucleus accumbens core (NAc) mediates the reinstatement of cocaine-seeking primed by drug-associated cues, context, and cocaine itself (LaCrosse et al 2016; McFarland et al 2003; Smith et al 2017). Accordingly, antagonism of NAc glutamate receptors, such as AMPA (Cornish and Kalivas 2000; Xie et al 2012) and mGlu5 (Wang et al 2013) receptors, attenuates the reinstatement of cocaine-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of nNOS interneurons is most likely mediated via a direct effect of glutamatergic afferents as anatomical studies have shown that these neurons express NMDA receptor mRNA (Price et al, 1993) and protein (Gracy and Pickle, 1997). Recent studies by Kalivas and colleagues have also shown that selective activation of metabotropic glutamate receptor 5 also stimulates NO release from nNOS interneurons in the NAc core (Smith et al, 2017). Taken together, these studies indicate that graded, phasic activation of afferents from the fimbria stimulate NO production via glutamatergic activation of nNOS activity.…”
Section: 4 Discussionmentioning
confidence: 99%